Malam Tirakatan Manifestations of Harmony and Religious Nationalism in The Muslim Tradition of Yogyakarta - Qiptiyah, Titin Mariatul; Arifin, Zainal; Rizal, Syaiful (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Malam Tirakatan or Malam Pitulasan is a local tradition of the people of Yogyakarta held to commemorate Indonesia's Independence Day on the night of 16 August, before the commemoration of 17 August. This tradition is not only a moment of reflection for the community, but also full of spiritual meaning and Javanese culture. The research will review Malam Tirakatan as a tangible manifestation of community harmony and nationalism reflected in local traditions based on religious values. The research uses a qualitative method with triangulation used to collect data. The research locations were Sambilegi Lor in Sleman Regency and Worawari in Kulon Progo Regency. The research found that the meaning of Malam Tirakatan goes beyond the mere celebration of independence; this tradition illustrates the values of spirituality, harmony, tolerance and gratitude to God and the heroes. In addition, Malam Tirakatan also shows how Javanese local wisdom acculturates religious nationalism with their culture, making it a means of strengthening Islamic religious identity.